Effect of luminance noise on the object frequencies mediating letter identification - Hall, Cierra; Wang, Shu; Bhagat, Reema; McAnany, J. Jason (Frontiers in Psychology, 2014)
Purpose: To determine if the same object frequency information mediates letter contrast threshold in the presence and absence of additive luminance noise (i.e. “noise-invariant processing”) for letters of different size. Methods: Contrast thresholds for Sloan letters ranging in size from 0.9 to 1.8 log MAR were obtained from three visually normal observers under three paradigms: 1) high- and low-pass Gaussian filtered letters were presented against a uniform adapting field; 2) high- and low-pass Gaussian filtered letters were presented in additive white luminance noise; and 3) unfiltered letters were presented in high- and low-pass Gaussian filtered luminance noise. A range of high- and low-pass filter cutoffs were used to limit selectively the object frequency content of the letters (paradigms 1 and 2) or noise (paradigm 3). The object frequencies mediating letter identification under each paradigm were derived from plots of log contrast threshold vs. log filter cutoff frequency. Results: The object frequency band mediating letter identification systematically shifted to higher frequencies with increasing log MAR letter size under all three paradigms. However, the relationship between object frequency and letter size depended on the paradigm under which the measurements were obtained. The largest difference in object frequency among the paradigms was observed at 1.8 log MAR, where the addition of white noise nearly doubled the center frequency of the band of object frequencies mediating letter identification, compared to measurements made in the absence of noise. Conclusions: Noise can affect the object frequency band mediating letter contrast threshold, particularly for large letters, an effect that is likely due to strong masking of the low frequency letter components by low frequency noise checks. This finding indicates that noise-invariant processing cannot necessarily be assumed for large letters presented in white noise.